Efeitos do comitê de auditoria e do conselho fiscal na qualidade da informação contábil no Brasil - Baioco, Vitor Gomes (2015)
This dissertation was developed in order to investigate the installation and characteristics effects of the Fiscal Council and the Audit Committee on the quality of accounting information in Brazil. The characteristics studied were independence and qualification of members. The proxies for accounting information quality were value relevance, timeliness and conditional conservatism. The sample was composed by Brazilian companies listed on the Securities, Commodities, and Futures Exchange (BM&FBovespa), with annual liquidity over 0,001 in the period of years 2010 to 2013. The data were collected from Comdinheiro database and Reference Forms, available on the website of the CVM or BM&FBovespa. The information models were adapted to the methodological approach and estimated by the method of ordinary least squares (OLS) with robust standard errors clustered by firm. The results revealed the purpose of installation of the institutions analyzed on the proxies of accounting information quality. The installation of the Fiscal Council positively impacted the relevance of net equity, while the installation of the Audit Committee impacted the relevance of earnings. These results may indicate differences in the attention of these institutions: to protect the organization’s equity for shareholders (Fiscal Council) or to ensure more trusted numbers on the managers’ performance (Audit Committee). In parallel, the results for the installation of Permanent Fiscal Council has inferred strength of this institution as control mechanism, rather than the installer only at the request of the shareholders. However, the implementation of Powered Fiscal Council was inefficient in controlling of the accounting information quality. In the characteristics analysis, the Audit Committee members’ independence impacted the relevance of earnings. While the Fiscal Council members’ independence impacted the relevance of net equity and impacted the conditional conservatism (timely recognition of economic losses). These associations were more significant when the Fiscal Council members were independent of the controlling shareholders. In the members’ qualification analysis, were found positive evidences between the relevance of net equity and a higher proportion of Council Fiscal members with qualification in Business (Accounting, Administration and Economy). The conditional conservatism was higher when the Fiscal Council members’ qualification converged to Accounting. The results of the Audit Committee members’ qualification demonstrated relevance of earnings in the presence of at least one Accountant, and at higher proportion of members with qualification in both Accounting and Business; being more significant when the Audit Committee members’ qualification converged to Accounting